HEALING FOREST AREA POTENTIAL ON THE MAIN CAMPUS OF THE UNIVERSITY OF BENGKULU - Surya Mardiana; Wiryono; Edi Suharto (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
ABSTRACT The prevalence of mental health problems among urban dwellers is triggered mainly by increased urbanisation and the pressures of modern life. One solution that is now widely considered is the development of healing forests, which are green areas that serve as natural therapeutic spaces for mental and physical health. The University of Bengkulu's main campus, situated in a lush green area, has excellent potential to develop a healing forest. This study aims to analyse the potential for developing a healing forest on the Main Campus of the University of Bengkulu, including identifying suitable areas, analysing the benefits that can be generated, and recommending sustainable management and environmental conservation strategies. Through a qualitative descriptive approach, data were collected through direct observation, interviews with relevant parties, and literature review. The results showed that, after evaluation, the location that qualifies as a healing forest is only in zone 2, specifically at the point where the green area around the UNIB Rectorate is located. However, other places have the potential to be developed into a healing forest. Based on an analysis of visitors' perceptions and preferences, it is suggested that each location has the potential to be a healing forest, with several recommendations provided. Developing a healing forest on this campus is expected to be a strategic step in creating an environment that supports the psychological well-being of the academic community and provides broader ecological benefits. Keywords: Healing forest, green area, nature therapy, mental health, University of Bengkulu